STRATEGI KEBERHASILAN BADAN USAHA MILIK DESA (BUMDES) AMANAH SEJAHTERA DI DESA SUNGAI BULUH KECAMATAN SINGINGI HILIR - Alfi Syahra; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Establishment of Village Owned Enterprises (BUMDes) is one way to make an innovation in improving village development and its people in the economic field. This study aims to determine the success strategies undertaken by the BUMDes Amanah Sejahtera in Sungai Buluh Village, Singingi Hilir District which has been formed with many business units which are one example of BUMDes Succeed in Kuantan Singingi Regency in managing the assets of their village assets. This study also aims to find out how the success of the Amanah Sejahtera Village Owned Enterprises (BUMDes) in Sungai Buluh Village Singingi Hilir District and the supporting factors for the success of the Amanah Sejahtera Village Owned Enterprises (BUMDes). The results of this study indicate that, first the strategy of the Village Owned Enterprises (BUMDes) Amanah Sejahtera that has been done It has been going quite well and in accordance with the objectives, vision and mission of BUMDes Amanah Sejahtera can be seen in the process of developing BUMDes with increasing profits that continue to increase three years successively also won the title as the Best Village-Owned Enterprises (BUMDes) in Kuantan Singingi Regency. Second, the supporting factors for the success of a village-owned enterprise (BUMDes) from the Prosperous Trust starting from creating to managing each business unit so as to achieve success and success. The Establishment of a Village-Owned Enterprises (BUMDes) Amanah Sejahtera in Sungai Buluh Village until the implementation of various activities and activities has in fact been able to provide economic changes more than before, several other supporting factors such as the character of the director of the Village-Owned Enterprises (BUMDes) and public trust make the Agency The Amanah Sejahtera Village Owned Enterprise (BUMDes) continues to grow and progress until it is awarded as the best BUMDes at the regency level. Keywords: Strategy, Success of Village Owned Enterprises (BUMDES)